A legal study on right of civil servants under the contractual based employment / Harold Emparak Kerebo … [et al.] - Kerebo, Harold Emparak; Abdul Razak, Aza Hartini; Mohd Azizi, Nur Nabiha; Geoffrey, Siti Nooraishah; Habibullah, Siti Anis (2010)
The purpose of this study are to highlight and examine problems faced by civil servants on contract based employment and to discover possible solutions to the problem faced by the contract based employees. Employment of contract based employees are sometimes needed due to the fact that the service is needed only for a short duration and nature of work are more suitable by contract employees and not permanent employees. The findings show that employees under contract of service are granted benefits similar to permanent basis employees such as medical allowance, housing allowance and travelling allowance. The denial of such employment benefits are only for employees whom are under for service.